2007
DOI: 10.1111/j.1365-2664.2006.01262.x
|View full text |Cite
|
Sign up to set email alerts
|

Seed dispersal and recruitment limitation are barriers to native recolonization of old‐fields in western Australia

Abstract: Summary1. Native recolonization of abandoned farmland in the wheat-growing region of western Australia is slow to non-existent, even 45 years after abandonment. Instead, old-fields tend to be dominated by non-native annual grasses. The native vegetation in the region is highly fragmented. We predicted that recovery is limited by seed availability and recruitment failure. 2. We compared the seed rain, soil seed bank and extant vegetation of three old-fields and three adjacent native woodland remnants to test ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
146
2
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 167 publications
(153 citation statements)
references
References 49 publications
(83 reference statements)
2
146
2
1
Order By: Relevance
“…Seed limitation of typical native grassland species and presence of annual non-natives in disturbed old-fields areas has been observed in other studies in the southern hemisphere (Tognetti et al 2010, Standish et al 2007. Our study, together with the few other available studies of the seed bank of subtropical Campos Sulinos grasslands in Brazil, indicates that the large majority of typical grassland species depend on vegetative regrowth from rhizomes or underground storage organs after a disturbance (Fidelis et al 2014), or that are short lived in the soil and that regeneration from the seed bank is not the principal plant strategy.…”
Section: Contribution Of Seed Bank Studies Of Our Understanding Of Vementioning
confidence: 81%
“…Seed limitation of typical native grassland species and presence of annual non-natives in disturbed old-fields areas has been observed in other studies in the southern hemisphere (Tognetti et al 2010, Standish et al 2007. Our study, together with the few other available studies of the seed bank of subtropical Campos Sulinos grasslands in Brazil, indicates that the large majority of typical grassland species depend on vegetative regrowth from rhizomes or underground storage organs after a disturbance (Fidelis et al 2014), or that are short lived in the soil and that regeneration from the seed bank is not the principal plant strategy.…”
Section: Contribution Of Seed Bank Studies Of Our Understanding Of Vementioning
confidence: 81%
“…Chief among the changes that are difficult to reverse are missing soil seed banks, nutrient enrichment, the presence of competitive non-native species, and reduced seed sources and land degradation associated with habitat fragmentation (Standish et al , 2007(Standish et al , 2008. Socio-economically, there is not the current knowledge to recover all facets of the historic ecosystem (e.g., native ground cover), and additionally there is not the needed level of investment to discern methods to do so.…”
Section: Novelty and Novel Ecosystemsmentioning
confidence: 99%
“…At the experimental site, ecological and socio-economic thresholds are present which indicated that restoration to historic York gum woodland would likely be prevented (Standish et al 2007). Chief among the changes that are difficult to reverse are missing soil seed banks, nutrient enrichment, the presence of competitive non-native species, and reduced seed sources and land degradation associated with habitat fragmentation (Standish et al , 2007(Standish et al , 2008.…”
Section: Novelty and Novel Ecosystemsmentioning
confidence: 99%
“…The observed gradient strongly supports the initial floristic composition model by Egler (1954) and the strong and persistent influence of the land use history on the plant community and the pathway of succession, respectively (Koerner et al 1997;Dupouey et al 2002;Bonet 2004;Dölle and Schmidt 2007). Which species dominate during succession can be determined by numerous factors like differences in seed dispersal, interannual differences in seed production (mast years), soil seed bank, germination requirements, relative growth rate, competition with other plant species, as well as various environmental parameters (Hard 1975;Schmidt 1981;Tilman 1988;Zeiter et al 2006;Standish et al 2007).…”
Section: Effects Of Successional Changes On Soil Chemical Properties mentioning
confidence: 99%